Chip formation studies in machining fibre reinforced polymer composites. (1st January 2013) - Azmi, A.I.
The use of end milling process for machining of fibre reinforced polymer composites has been widespread in various industries. Until recently, very little work has been reported with regard to characterisation of chip formation mechanisms while end milling these composite materials. This paper reports such study which was accomplished via high speed photography and quick stop procedure. It is apparent that the heterogeneity and insufficient ductility of the composites have produced discontinuous and fracturing chips. Information disclosed by the high-speed photography footages has shown that a layer of delaminated chip was formed as the tool cutting edge fractured the workpiece along the fibre orientation at the lowest cutting speed. The increased cutting speed accelerates the fracture of chips into smaller segments, which make it difficult to denote any chip formation processes. Similarly, shorter chip fragments were created as the tool cut at different fibre orientation (45° and 90° with respect to tool feed direction).